A Missense De Novo Variant in the CASK-interactor KIRREL3 Gene Leading to Neurodevelopmental Disorder with Mild Cerebellar Hypoplasia - Ciaccio, Claudia; Leonardi, Emanuela; Polli, Roberta; Murgia, Alessandra; D'Arrigo, Stefano; Granocchio, Elisa; Chiapparini, Luisa; Pantaleoni, Chiara; Esposito, Silvia (Neuropediatrics, 2021)
KIRREL3 is a gene important for the central nervous system development—in particular for the process of neuronal migration, axonal fasciculation, and synaptogenesis—and colocalizes and cooperates in neurons with CASK gene. Alterations of KIRREL3 have been linked to neurodevelopmental disorders, ranging from developmental delay, to autism spectrum disorder, to attention deficit/hyperactivity disorder. The underlying mechanism is not yet fully understood, as it has been hypothesized a fully dominant effect, a risk factor role of KIRREL3 partially penetrating variants, and a recessive inheritance pattern. We report a novel and de novo KIRREL3 mutation in a child affected by severe neurodevelopmental disorder and with brain magnetic resonance imaging evidence of mega cisterna magna and mild cerebellar hypoplasia. This case strengthens the hypothesis that dominant KIRREL3 variants may lead to neurodevelopmental disruption; furthermore, given the strong interaction between KIRREL3 and CASK, we discuss as posterior fossa anomalies may also be part of the phenotype of KIRREL3-related syndrome.
Keywords: KIRREL3; developmental disorders; developmental delay; cerebellar hypoplasia; pediatric ataxia